Stochastic National Income - Wei, Taoyuan (Journal of Reviews on Global Economics, 2012)
Abstract: How can national income be adjusted to indicate welfare improvement if the future is uncertain? The present paper extends the definition of national income to stochastic settings on the basis of discounted utilitarian welfare function. Real interest rate of consumption is redefined so that real national income can be interpreted as the expected present value of real interest on future national consumption. A stochastic one-good model is used to illustrate the application of the stochastic real national income. It turns out that under uncertainty real national income may be decreasing even though captial stock is constant or increasing over time.